Hepatic arterial infusion chemotherapy and trastuzumab in gastric cancer with liver metastases: a case report - Li, Hui-qin; Wang, Qin; Zhang, Liu-yan; Li, Jia-yin; Wang, Ying-jie; Wei, Li; Yao, Li-ge (Frontiers in Oncology, 2023)
Background: Gastric cancer is a common cancer worldwide and is responsible for over one million new cases in 2020 and an estimated 769,000 deaths, ranking fifth for incidence and fourth for mortality globally. Incidence rates are highest in Eastern Asia and Eastern Europe. Gastric cancer is highly heterogeneous and progresses rapidly. The prognosis of gastric cancer with liver metastases is poor, and clinical treatment remains challenging. Human epidermal growth factor receptor 2 (HER2) positivity is correlated to a bad prognosis for gastric cancer. Trastuzumab combined with systemic chemotherapy is the preferred treatment for HER2-positive advanced gastric cancer. However, intravenous chemotherapy has severe systemic toxicity, which reduces the local drug concentration and tumor uptake rate, and the effect is unsatisfactory. Case summary: We reported a 66-year-old patient with HER2-positive advanced gastric cancer with jaundice due to multiple liver metastases, after 6 cycles of trastuzumab combined with hepatic arterial infusion chemotherapy (HAIC), the tumor retracted significantly, the jaundice subsided, and the patient recovered well. The patient achieved disease control with an intensive regimen followed by less toxic maintenance therapy. Trastuzumab combined with capecitabine maintenance therapy followed up for more than 16 months.HAIC plus trastuzumab may be a tolerable treatment option for patients with severe liver metastases from HER2-positive gastric cancer to achieve local control and prolong survival.